Analysis of Character Values in the Traditional Game Bentengan in Basketball Material - Ndona Nasugian; Utvi Hinda Zhannisa; Sugeng Sugeng; Muh. Isna Nurdin Wibisana (PHEDHERAL, 2024)
This research aims to analyze the values of character education present in the traditional game Bentengan within basketball material at SMKN 4 Semarang. The research method used is qualitative. Data collection techniques include interviews, documentation, and observation. Data analysis was conducted through data collection, reduction, presentation, and conclusion drawing. The subjects of this research are 36 students from class XI, majoring in mechanical engineering 1, divided into 2 groups for the traditional game Bentengan. The study results indicate the implementation of character values through the Bentengan game among class XI students of Mechanical Engineering 1 at SMKN 4 Semarang, including good communication, honesty, sportsmanship, risk-taking courage, leadership, adherence to rules, and fairness. From this research, it can be concluded that the traditional game Bentengan can be used to form and develop students' character within basketball material.